Gesundheitsökonomische Analyse der medizinischen Trinknahrungen in Deutschland - Nuijten, M.; Mittendorf, T. (Aktuelle Ernährungsmedizin, 2012)
Purpose: To assess the health economic impact of oral nutritional supplement (ONS), being a medical nutrition product in the community setting in Germany in 2007.Methods: This health economic analysis is based on a comparison of the use of ONS versus no use of ONS in patients, who are eligible for ONS due to (risk of) disease-related malnutrition (DRM). The costs of the two treatment strategies, “ONS” versus “no ONS” were assessed using a linear decision analytic model reflecting cost functions related with DRM. Data sources are based on the published literature, clinical trials, official national price/tariff lists and national population statistics.Results: This study shows that the extra costs for ONS (€ 534) are off-set by a reduction of hospitalisation costs (€ 768) leading to total cost savings of € 234 per patient. A scenario analysis based on length of hospital stays and per diem costing instead of DRG costs shows that the extra costs for ONS (€ 534) are also off-set by a reduction of hospitalisation costs (€ 791) leading to cost savings of € 257 per patient. Additional scenarios showed similar and consistent results.Conclusions: This health economic analysis shows that the use of ONS leads to cost savings for the cost of DRM in Germany in the community setting. In addition the use of ONS leads also to better clinical outcomes due to a reduction of hospitalisations. As a consequence the use of ONS might be considered cost-effective at a patient and also a population level, which could be shown also in extensive sensitivity analyses.
Keywords: Oral Nutritional Supplement, ONS; malnutrition; cost analyses; Germany